PROTECTIVE EFFECT OF PHYTOCHEMICAL CONSTITUENTS ON OXIDATIVE & NON OXIDATIVE DNA DAMAGE INDUCED BY H2O2 & ASPIRIN - Dr. Eswari Beeram, P Govardhan, Dr. S. Hemachandra, S. Himagirish Kumar, Swetha Madamala (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Aspirin is a non steroidal anti inflammatory drug used widely due to its low cost and efficacy. Aspirin alone does not cause DNA damage but at certain situations like aspirin in water can induce DNA damage. H2O2 is generally used to induce oxidative stress and in this study we used 1% Aspirin dissolved in water and three different concentrations of H2O2 like 5%,15% and 25% to induce DNA damage. We studied protective effect of 10 phytochemical constituents like Lablab purpureus,Mangifera indica,Vigna unguiculata,Musa paradisiaca, Oryza sativa, Vigna radiata, Vigna mungo, Azadirachta indica, Ocimum sativum and Eucalyptus on DNA damage induced by aspirin and H2O2. In the 10 phytochemicals used Oryza sativa offered full protection commonly to all three concentrations of 5%,15% and 25% H2O2 used. Where as Lablab purpureus Ocimum sativum and Eucalyptus protected commonly with 5% and 25% H2O2.